The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s1415-47572007000100003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of glucose-6-phosphate dehydrogenase deficiency in patients from the southern Brazilian city of Porto Alegre, RS

Abstract: Glucose-6-phosphate dehydrogenase (G6PDH; EC 1.1.1.49) deficiency is one of the most common human enzymopathies throughout the world. Although most affected individuals are asymptomatic, there is a risk of neonatal jaundice and acute hemolytic anemia which can be triggered by infection, some pharmaceuticals and, in older individuals, eating fava beans. We characterized the molecular basis of G6PDH deficiency in a sample of 348 adults from Porto Alegre (population about 1.5 million), the capital of the southern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Although the frequency of G6PD deficiency in the study group was almost twice that of the controls (7.4 vs. 3.7%), it did not reach statistical difference, probably due to the small sample size. The mutations studied for G6PD are the most frequent in our state (15), and the overall prevalence of the deficiency in our sample (5.2%) is consistent with the 7.8% previously described in our population (16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 91%
“…Although the frequency of G6PD deficiency in the study group was almost twice that of the controls (7.4 vs. 3.7%), it did not reach statistical difference, probably due to the small sample size. The mutations studied for G6PD are the most frequent in our state (15), and the overall prevalence of the deficiency in our sample (5.2%) is consistent with the 7.8% previously described in our population (16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 91%
“…The frequency of the G6PD*A - variant among the Afro-descendants studied here (6.1%) is somewhat higher than that observed by Santana et al (2013) among males from the population of Manaus, state of Amazonas (3.8%) and by Dombrowski et al (2017) in males from the Juruá valley, state of Acre, northern Brazil. It is also higher than the frequency found by Castro et al (2007) in newborns from Porto Alegre, southern Brazil (2.9%), but is similar to those found in Campinas (6.1%) and São Paulo (5.8%), southeastern Brazil, by Mezzacappa et al (2010) and Oliveira et al (2009) , respectively. On the other hand, the frequency of G6PD*A- in the current study is lower than the frequency of 8.2% reported by Moura-Neto et al (2008) for the population of Salvador, Bahia, northeastern Brazil, a population of predominantly African origin ( Santos et al , 2016 ).…”
Section: Discusssionsupporting
confidence: 65%
“…One study showed that patients who received blood donated by G6PDd individuals did not develop haemolysis, even though some were using drugs that could potentially trigger this complication [ 15 ]. Some studies showed a higher frequency of previous history of jaundice in G6PDd in relation to non-G6PDd individuals [ 16 ], or a higher frequency of G6PDd in patients with history of acute haemolytic crises in comparison with the general population [ 17 ]. However, haemolysis caused by G6PDd was generally mild [ 16 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Favism and infection-induced haemolysis appear to play only a minor public health role in this continent. In general, in population-based studies carried out in regions where malaria is not endemic, individuals did not show a great risk of developing G6PDd-related haemolysis in their lifetimes [ 11 - 14 , 16 , 18 , 19 ], despite the establishment of an association between jaundice or history of haemolysis with G6PDd by some authors [ 16 , 17 ]. Another important finding in this context is the difficulty in linking G6PDd-related haemolysis with a specific stressor drug [ 20 , 22 , 23 , 25 , 26 , 126 , 127 ].…”
Section: Discussionmentioning
confidence: 99%